A triple‐win scenario for horizontal collaboration in logistics: Determining enabling and key success factors. (26th March 2019) - Palmieri, Antonio; Pomponi, Francesco; Russo, Angeloantonio
Abstract: Horizontal collaborations emerged as a new strategic option in the logistics sector during the last decade. However, successful implementation of horizontal collaborations is far from a developed issue due to several barriers that exist or emerge when setting up such collaborative projects. This study aims at identifying the enabling factors supporting successful implementation of horizontal collaborations in the logistics sector, and in identifying key success factors that logistics service providers (LSPs) should consider. Results from a within‐ and cross‐case analysis of two horizontal collaboration projects in the contract logistics sector support the proposed theoretical framework, highlighting both enabling and key success factors of horizontal collaborations. The former refers to factors that are related to LSPs, customers, and industries, whereas the latter results in a triple‐win scenario characterised by LSP competences, trust, and environmental management orientation of successful horizontal collaboration projects.